Re-mining the collections: From bioprospecting to biodiversity offsetting in Madagascar. (November 2015) - Neimark, Benjamin D.; Wilson, Bradley
Highlights: Critical historical analysis of bioprospecting and biodiversity offsetting. A less studied output of bioprospecting are mass botanical herbarium collections. We trace the bioprospecting collections now digitized for biodiversity offsetting metrics. We examine labour in re-mining bioprospecting biodata for market legibility. Scientific institutions develop unevenly under market-based conservation. Abstract: Madagascar has always held a special place on the bioprospecting map. Designated as one of the world's "hottest" biodiversity hotspots, scientists believe the extremely high flora and faunal endemism contain unique potential for the commercialisation of natural products. Years of collections by bioprospectors in Madagascar are beginning to pay off, not necessarily from drug discovery, but through the biodata from their botanical collections. In the paper, we highlight the links between labour and value over time to illustrate the historical process of collecting inventories of biodata and calculating biodiversity metrics. As we demonstrate, biodata originally used for the purposes of drug discovery and scientific exploration are now being repurposed in biodiversity offsetting programs for multinational mining operations in Madagascar. This project of "re-mining" biodata has reinforced the power of select research institutions which now service their expertise for biodiversity offsetting initiatives. In sum, botanical agencies are far from apolitical actors in these new iterations of market-conservation but active participants in a new age of green grabbing.